Associations of Urinary Perchlorate, Nitrate, and Thiocyanate with Female Infertility and Mediation of Obesity: Insights from NHANES 2013–2018 - Lan Zhang; Yuhe Peng; Yue Song; Yu Zhang; Qi Qin; Mengya Ying; Yiyun Bi; Ping Yin (Toxics)
Classified as endocrine disrupting chemicals (EDCs), perchlorate, nitrate, and thiocyanate have been implicated with obesity and reproductive disorders. This study used three cycles of the National Health and Nutrition Examination Survey (NHANES 2013–2018); 813 women of reproductive age were finally included. We used multivariable logistic regression to analyze the associations between the three anions and obesity and infertility. Subsequently, we performed mediation analysis to explore the potential mediating effect of obesity on infertility in association with anion exposure. Increased concentrations of perchlorate and nitrate showed inverse correlations with the risk of obesity (OR = 0.73, 95% CI: 0.55–0.96; OR = 0.59, 95% CI: 0.40–0.87). Perchlorate was negatively associated with infertility (OR = 0.68, 95% CI: 0.51–0.91), and obesity was a mediator in association between perchlorate and infertility. These findings suggest that women of reproductive age may be protected from obesity and infertility by exposure to perchlorate and nitrate, with obesity acting as a moderating factor in the observed association. This study provides a valuable understanding of the complex links between environmental contaminants, obesity, and reproductive health, and identifies potential strategies to reduce the risk of infertility and improve women’s health.